Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to show that:

$$\lim\limits_{n\to\infty}{n(\sqrt[n]{n}-1)} = \infty$$

From what I've tried now, all I end up with is basically rewriting the left term as:


and then applying De L'Hôpital's rule (which gets really messy considering that we're deriving $\sqrt[n]{n}$, since $\frac{d}{dn}\sqrt[n]{n} = -n^{\frac{1}{n}-2}(\ln(n)-1)$).

Is there any "nice and quick" way to solve this?

share|cite|improve this question
up vote 10 down vote accepted

Note that $x^{1/x}=e^{(\ln x)/x}$. By looking at the power series expansion of $e^t$, we get that if $x\gt 1$ then $e^{(\ln x)/x}\gt 1+\frac{\ln x}{x}$. Now we are finished.

We can prove $e^t\gt 1+t$ if $t\gt 0$ in other ways, for example by looking at the derivative of $e^t$.

Remark: The advantage of the above approach is not so much quickness, though it is quick. What is useful is that it gives a quite precise idea of the size of $\sqrt[n]{n}-1$ for large $n$.

share|cite|improve this answer

You should always check to see if a change in variables would make the problem easier. I will use $n = \frac{1}{h}$.

$$\lim\limits_{n\to\infty}{n(\sqrt[n]{n}-1)} = \lim\limits_{n\to\infty}{n^{1+1/n}-n} = \lim\limits_{h\to0^+}{\frac{1}{h^{1+h}}-\frac{1}{h}}$$

Now just condense the fraction and work as normal.

$$\lim\limits_{h\to0^+}\frac{1}{h\cdot h^h}-\frac{1}{h} = \lim\limits_{h\to 0^+}\frac{1-h^h}{h\cdot h^{h}} $$

L'hopitals rule(s):

$$\lim\limits_{h\to 0^+}\frac{-(1+\log h)}{1+h + h\log h} $$

$$\lim\limits_{h\to 0^+}\frac{-\frac{1}{h}}{2 + \log h} $$

$$\lim\limits_{h\to 0^+}\frac{\frac{1}{h^2}}{\frac{1}{h}} $$

$$\lim\limits_{h\to 0^+}\frac{1}{h} = \infty$$

share|cite|improve this answer
This may not be the quickest way, but I like your solution— it is very easy to follow. +1. – chiru Jun 12 '14 at 3:52

For large values of $n$, an asymptotic development gives $$\sqrt[n] n=1-\frac{\log \left(\frac{1}{n}\right)}{n}+\frac{\log ^2\left(\frac{1}{n}\right)}{2 n^2}-\frac{\log ^3\left(\frac{1}{n}\right)}{6 n^3}+O\left(\left(\frac{1}{n}\right)^4\right)$$ from which you can also reach the conclusion.

For sure, you can obtain the same writing, as already told by André Nicolas, that $\sqrt[n] n=e^{\frac{\log(n)}{n}}$ and develop as a Taylor series.

share|cite|improve this answer

This is almost obvious if one recognizes that $\lim_{n \to \infty}n(\sqrt[n]{x} - 1) = \log x$. And it is easy to show that the sequence $y_{n} = n(\sqrt[n]{x} - 1)$ is decreasing and hence $y_{n} \geq \log x$. If $z_{n} = n(\sqrt[n]{n} - 1)$ then $z_{n} > y_{n} \geq \log x$ if $n > x$. Since $\log x \to \infty$ as $x \to \infty$, it follows that $z_{n} \to \infty$ as $n \to \infty$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.